ENGLISH TEACHING AS A TOOL FOR STUDENTS’ PERSONAL GROWTH, SOCIAL DEVELOPMENT, AND INSTILLING VALUES OF GLOBAL AWARENESS: EXPERIENCE AND PROBLEM SOLVING - Kudritskaya, М.; Kopeikina, L. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The lessons analyzed in the present article –Writing a Story, Writing an Opinion Essay, and Things You Didn’t Know About Space–implicitly and explicitly teach a wide range of values that extend beyond language learning. These lessons promote values tied to personal growth, social development, and global awareness, making them not only educational but also transformative. The authors share their teaching experience, analyze the challenging issues and provide recommendations for their colleagues.
Keywords: English language teaching; personal growth; social development; global awareness; holistic approach